Doing patient-centredness versus achieving public health targets: a critical review of interactional dilemmas in ART adherence support - De Kok, B.C.; Widdicombe, S.; Pilnick, Alison; Laurier, E. (Elsevier, 2018)
Anti-retroviral Therapy (ART) transformed HIV into a chronic disease but its individual and public health benefits depend on high levels of adherence. The large and rising number of people on ART, now also used as prevention, puts considerable strain on health systems and providers in low and middle as well as high-income countries, which are our focus here. Delivering effective adherence support is thus crucial but challenging, especially given the promotion of patient-centredness and shared decision making in HIV care. To illuminate the complexities of ART adherence support delivered in and through clinical encounters, we conducted a multi-disciplinary interpretative literature review. We reviewed and synthesized 82 papers published post 1997 (when ART was introduced) belonging to three bodies of literature: public health and psychological studies of ART communication; anthropological and sociological studies of ART; and conversation analytic studies of patient-centredness and shared decision-making. We propose three inter-related tensions which make patient-centredness particularly complex in this infectious disease context: achieving trust versus probing about adherence; patient-centredness versus reaching public health targets; and empowerment versus responsibilisation as ‘therapeutic citizens’. However, there is a dearth of evidence concerning how precisely ART providers implement patient-centredness, shared-decision making in practice, and enact trust and therapeutic citizenship. We show how conversation analysis could lead to new, actionable insights in this respect.